2021
DOI: 10.3390/su131911022
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Modeling and Prediction Method for Sustained Rainfall-PM2.5 Removal Modes on a Micro-Temporal Scale

Abstract: PM2.5 is unanimously considered to be an important indicator of air quality. Sustained rainfall is a kind of typical but complex rainfall process in southern China with an uncertain duration and intervals. During sustained rainfall, the variation of PM2.5 concentrations in hour-level time series is diverse and complex. However, existing analytical methods mainly examine overall removals at the annual/monthly time scale, missing a quantitative analysis mode that applies micro-scale time data to describe the rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…atures becomes smaller as the flue gas velocity increases, which shows that the temperature has less influence on the grade efficiency at high flue gas velocity. (5) In the presence or absence of a magnetic field, the higher the temperature, the lower the weakened gradient of the flue gas velocity on the grade efficiency, which suggests that the increase in temperature reduces the influence of the flue gas velocity on the grade efficiency. To gain a clearer understanding of the relationship between magnetic field and flue gas velocity, the grade efficiency with and without a magnetic field at 873 K and at different flue gas velocities can be obtained based on Figure 10, as shown in Figure 13: (1) At the same temperature, the difference in grade efficiency among different flue gas velocities gradually decreases and flattens with the increases in particle size, indicating that the magnetic field has a more pronounced effect on enhancing the grade efficiency of smaller particle sizes.…”
Section: Simulation and Prediction Of Magnetic Field Effect Under Dif...mentioning
confidence: 99%
See 1 more Smart Citation
“…atures becomes smaller as the flue gas velocity increases, which shows that the temperature has less influence on the grade efficiency at high flue gas velocity. (5) In the presence or absence of a magnetic field, the higher the temperature, the lower the weakened gradient of the flue gas velocity on the grade efficiency, which suggests that the increase in temperature reduces the influence of the flue gas velocity on the grade efficiency. To gain a clearer understanding of the relationship between magnetic field and flue gas velocity, the grade efficiency with and without a magnetic field at 873 K and at different flue gas velocities can be obtained based on Figure 10, as shown in Figure 13: (1) At the same temperature, the difference in grade efficiency among different flue gas velocities gradually decreases and flattens with the increases in particle size, indicating that the magnetic field has a more pronounced effect on enhancing the grade efficiency of smaller particle sizes.…”
Section: Simulation and Prediction Of Magnetic Field Effect Under Dif...mentioning
confidence: 99%
“…They found that the number of publications on PM2.5 exposure has been increasing at an accelerating rate. Wu et al [5] proposed a quantitative modeling and prediction method for sustained rainfall-PM2.5 removal modes on a micro-temporal scale, citing the reasonableness and effectiveness of the proposed method.…”
Section: Introductionmentioning
confidence: 99%